Financial stress predictors for civil service sector employees - A. R., Husniyah; O., Mohd. Amim; S., Mohamad Fazli; M., Amirah Shazana (Malaysian Consumer and Family Economics Association, 2019)
The service provided for the public may be affected by financially stress employees. This study aims at identifying financial stress predictors among 470 Malaysian civil servants via a multi-stage random sampling through a cross-sectional survey. Financial problem was revealed to be the most influencing on financial stress followed by financial adequacy and work-life balance. Investment and health status also contribute to financial stress. The results will assist employers to develop financial education or coping with stress programs in enhancing the quality of services. Time can thus be used efficiently and productively by both parties enabling the growth in the economy.